Occupational segregation by race in South Africa after apartheid - Carlos Manuel Gradín Lago (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper investigates progress in reducing the high level of racial stratification of occupations after apartheid in South Africa. Empirical analysis, using census microdata and Labour Force Surveys, does not provide strong evidence of sustained or significant desegregation. Occupations remain highly segmented by race, with blacks disproportionally holding low-paying jobs (compared with whites). Less than a third of segregation and about half of racial stratification in occupational distribution are related to blacks' characteristics, especially their lower educational achievement, a gap that has been reduced over time. Segregation and stratification, however, remain when blacks and whites with similar characteristics are compared.
Keywords: J15; J42; J71; J82; O15; O55; 330; occupational segregation; stratification; low-paying; apartheid; South Africa; race